2017
DOI: 10.1177/0886260516683176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perceived Femininity, Masculinity, Race/Ethnicity, and Socioeconomic Status on Intimate Partner Violence Among Sexual-Minority Women

Abstract: Sexual minority women (SMW) are believed to experience comparable or higher rates of intimate partner violence (IPV) than heterosexual women. In this study we expand upon existing research by examining the intersectional relationships among self-perceptions of femininity and masculinity, race/ethnicity, socioeconomic status and IPV. Data are from the most recent wave of the longitudinal Chicago Health and Life Experiences of Women (CHLEW) study that included a diverse sample of SMW (N=608). We use multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 60 publications
1
44
0
2
Order By: Relevance
“…It was also found that participants with a low economic status and high education levels were often both victims and perpetrators of sexual violence in intimate relationships. These findings suggest that power imbalance has an impact on the prevalence and frequency of IPV (Milletich et al, 2014; Steele et al, 2020). Previous studies have reported that individuals with feelings of inadequacy engage in violence to gain power (McKenry et al, 2006; Rohrbaugh, 2006).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It was also found that participants with a low economic status and high education levels were often both victims and perpetrators of sexual violence in intimate relationships. These findings suggest that power imbalance has an impact on the prevalence and frequency of IPV (Milletich et al, 2014; Steele et al, 2020). Previous studies have reported that individuals with feelings of inadequacy engage in violence to gain power (McKenry et al, 2006; Rohrbaugh, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…The limited number of studies investigating IPV in same-sex relationships have focused on IPV in lesbian and bisexual women. Assumptions that women do not commit physical violence, that physical violence against men is not possible, and that this type of violence is more easily managed in same-sex relationships than heterosexual relationships have reduced the importance of same-sex IPV (Renzetti, 1992; Steele, Everett, & Hughes, 2020; Whitton, Dyar, Mustanski, & Newcomb, 2019). Furthermore, unlike most heterosexual women, women who are members of sexual minority groups face many additional stressors due to the stigma related to their sexuality and sexual orientation in a society that does not approve of their relationships (Balsam & Szymanski, 2005; Fingerhut, Peplau, & Ghavami, 2005; Brown, 2008; Messinger, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Further, in this study, we used two singleitem measures of perceived masculinity and femininity which likely do not capture the multifaceted nature of gender expression. Single-items measures, however, have been used in other studies (Martin-Storey & August, 2016;Steele, Everett, & Hughes, 2017). The broad nature of the survey questions may actually be beneficial as femininity and masculinity may mean different things to SMW of differing races/ethnicities (Harris & Crocker, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Participants indicated their perceived femininity on a sliding scale that was anchored not at all feminine (0) and extremely feminine (100). For a similar single-item measure, see Steele, Everett, and Hughes (2017).…”
Section: Moderator Variable: Perceived Femininitymentioning
confidence: 99%